Investigation of the Genetic Basis of Antibiotic Resistance in Mycobacterium tuberculosis - Evans, Joanna (Division of Medical Microbiology, 2023)
The emergence of antibiotic resistant strains of Mycobacterium tuberculosis, coupled with the time it takes to perform phenotypic drug susceptibility testing of this organism, makes the treatment of tuberculosis increasingly difficult. Several genotypic assays for the rapid detection of drug resistance in M. tuberculosis have been developed, but the sensitivity with which these assays identify resistance differs geographically. Additionally, the identification of phenotypically resistant isolates with no identifiable genotypic marker suggests that other factors, such as differential gene expression, may play a role in the development of drug resistance in M. tuberculosis. This investigation aims to both develop and evaluate rapid genotypic assays for the detection of resistance to both first- and second-line drugs in M. tuberculosis, and to investigate the role of alternative sigma factors in the progression to multidrug resistant M. tuberculosis. The sensitivity of the GenoType® MTBDRplus [HAIN Life science] assay for the detection of rifampicin and isoniazid resistance was evaluated in clinical M. tuberculosis isolates with varying phenotypic susceptibility profiles from Cape Town, South Africa. Additionally, the use of multiplex allele-specific-PCR assays for the detection of two commonly identified isoniazid resistance determinants was evaluated in parallel. The GenoType® MTBDRplus [HAIN Lifescience] assay identified rifampicin and isoniazid resistance in clinical M. tuberculosis isolates with sensitivities of 93.5% and 82.1%, respectively, and similar results were obtained using multiplex allele-specific-PCR assays for the detection of isoniazid resistance. Novel multiplex allele-specific-PCR assays for the detection of resistance to ofloxacin and kanamycin/amikacin in M. tuberculosis were designed, and their ability to correctly identify resistance to these second-line drugs was evaluated. Multiplex allele-specific-PCR assays for the detection of GyrA D94G and rrs A1401G correctly identified ofloxacin and kanamycin/amikacin resistance in M. tuberculosis in 64.3% and 80.0% of phenotypically resistant isolates, respectively. Whilst the development of genotypic assays for the rapid detection of drug resistance in M. tuberculosis show promise, variation in the geographical distribution of specific resistance determinants necessitates that phenotypic drug susceptibility testing be performed in parallel. However, screening for GyrA D94G and A90V together with rrs A1401G would identify up to 88.0% of XDR-TB in this region prior to obtaining phenotypic drug susceptibility results, making these assays extremely useful as a rapid genotypic tool for the detection of second-line drug resistance in this setting. The role of alternative sigma factor expression in the progression to drug resistance in M. tuberculosis was investigated in rifampicin mono-resistant M. tuberculosis H37Rv isogenic mutants using real-time quantitative PCR assays. Investigation of rifampicin mono-resistant M. tuberculosis H37Rv isogenic mutants indicated an association between specific RpoB mutations and an enhanced ability to grow in the presence of isoniazid. Furthermore, mutants that were able to grow in the presence of isoniazid displayed upregulation of sigE, which encodes a sigma factor involved in the maintenance of cell wall structure. A role for differential gene expression induced by the use of alternative sigma factors in the development of drug resistance in M. tuberculosis was demonstrated in rifampicin mono-resistant M. tuberculosis H37Rv isogenic mutants, and further confirmed in clinical isolates of M. tuberculosis.